REMOTE SENSING APPLICATION TO INVESTIGATION AND ASSESSMENT OF SUSTAINABLE INDICATORS OF THE TYPICAL TIDAL ECOSYSTEMS IN HAl PHONG - QUANG NINH AREA - Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2007)
The results from processing and analyzing SPOT and Landsat images of time series to assess changing and development tendency of the ecosystems of mangroves and tidal flats by using the indicatators of square area show that: recent years, mangrove area has decreased dramatically; meanwhile aquaculture pond area has largely increased, particularly in the period after 2000. Similar to mangroves, tidal flat area has much decreased since 2000 and also related to the development of aquaculture ponds. The area of land filling in coastal area has a tendency of much increase since 2000, by factor of 2.5 only from 2002 to 2004, and mainly taken place in Ha  Long - Bai Tu Long area. With the direct corelation of spatial use of tidal flat and mangroves for development of aquaculture ponds and land filling in Quang Ninh, it is projected that the area for aquaculture development to 2010 will be about 20,000 ha and total area of mangrove and tidal flat will be in correspondence about 35,000 ha. For only mangroves, the area in Quang Ninh is predicted about 10,000 ha. With this area, mangrove ecosystem will have not enough environmental carrying capacity against wastes to be generated by aquaculture development